2021
DOI: 10.21037/apm-21-2329
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of various risk factors of death from emergency cerebrovascular diseases in the department of neurology

Abstract: Background: Cerebrovascular disease is one of the leading causes of death and disability in China.Preventive measures to reduce the incidence of cerebrovascular disease are important, so the risk factors associated with death need to be identified. Most studies showed that cerebrovascular disease has many risk factors for death, such as hypertension, hyperlipidemia, family history of stroke, diabetes, overweight, alcohol consumption, and smoking.Methods: A literature search was conducted in the English databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The latter subgroup was also found to experience more severe stroke symptoms [ 93 ]. One meta-analysis found a greater risk of stroke mortality in all patients with FHS [ 94 ]; three studies confirmed this in subgroups: younger age [ 77 , 95 ] and with parental FHS [ 11 , 77 ]; three studies did not show any association of FHS with mortality [ 91 , 96 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter subgroup was also found to experience more severe stroke symptoms [ 93 ]. One meta-analysis found a greater risk of stroke mortality in all patients with FHS [ 94 ]; three studies confirmed this in subgroups: younger age [ 77 , 95 ] and with parental FHS [ 11 , 77 ]; three studies did not show any association of FHS with mortality [ 91 , 96 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Death [11,77,91,[94][95][96][97] One study showed increased mortality among patients with FHS [94], three studies confirmed it in subgroups [77,95], others did not show this association [91,[96][97].…”
Section: Parameter Publications Correlationmentioning
confidence: 99%